E3 ligase Skp2-mediated stabilization of survivin contributes to radioresistance - Shiming Tan; Ruirui Wang; Jinglin Fang; Ming Yi; Pengfei Guo; Shuangze Han; Xiaoying Li; Yu Gan; Jinzhuang Liao; Xinfang Yu; Wei Li (Cell Death Discovery)
Abstract Oral squamous cell carcinoma (OSCC) is a frequently occurring neck and head malignancy. Therapies for OSCC are improving, but radiotherapy resistance remains a major clinical challenge. Here, we found that the S-phase kinase-associated protein 2 (Skp2) is overexpressed in OSCC cells and tissues. Knockdown of Skp2 significantly increased the radiotherapy sensitivity of OSCC cells. Further potential mechanisms suggest that Skp2-deficient restoration of radiotherapy sensitivity in OSCC cells may induce intrinsic apoptosis through inhibition of the Akt/Wee1/CDK1 axis, which inhibits Survivin phosphorylation and promotes its ubiquitination and degradation by FBXL7. Clinicopathologic histological analysis showed that Skp2 was positively correlated with the expression of p-Akt and Survivin in OSCC tissues. Furthermore, knockdown or inhibition of Skp2 overcame the radiotherapy resistance of OSCC cells. In conclusion, our study demonstrated that targeting the Skp2-Survivin axis could serve as an attractive and promising potential therapeutic target for radiotherapy sensitization in OSCC.